Analisa Karakter Fisiologis dan Hasil Tanaman Mentimun Suri (Cucumis melo) Terhadap Dosis Pupuk Kandang Sapi dan Pupuk Organik Cair - Alima Maolidea Suri; Windu Mangiring; Fizzaria Khasbullah (AGRORADIX : Jurnal Ilmu Pertanian, 2025)
Continuous use of inorganic fertilizers results in decreased Cucumis melo plant production. The use of organic materials is an alternative to increase soil fertility.This experiment used a split plot design with cow manure and liquid organic fertilizer 'KSM' doses. The doses of cow manure include 10 tons/Ha, 20 tons/Ha, and 30 tons/Ha and the doses of liquid organic fertilizer ‘KSM’ include 150 ml/tank, 250 ml/tank, dan 350 ml/tank. The observed observation variables consist of physiological characters and harvest results. Physiological characters consist of Leaf Area Index, Net Assimilation Rate, and Plant Growth Rate. Harvest results variables consist of fruit weight per plant, fruit diameter per plant, and fruit length per plant. From the observation results, it is then analyzed using analysis of variance at the level of α = 5%. If in the analysis of variance there is a significant difference between the treatments tested, to find out the different treatments, BNT is carried out at the level of α = 5%. The treatment of 30 tons/Ha of cow manure and 350 ml/tangki of “KSM” POC was able to improve the physiological characteristics and harvest yields of Cucumis melo, namely in the variables of leaf area index, fruit weight per plant, and fruit diameter.